(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The objective of this study was to evaluate correlations between production and economic variables of lactating cows on a tropical pasture. The experiment involved ten ¾ Holstein Ã— ¼ Dairy Gyr cows in the middle third of lactation at an average age of 70 ± 4.6 months and an average body weight of 400 ± 55.2 kg. Cows were supplemented with a concentrate feed with different supplement compositions aiming to promote alterations in the animal performance and economic responses. Data were analyzed statistically by Pearson correlations at the 0.95 probability level. No correlations were observed for fat and total solids with economic variables (p > 0.05). Milk yield was positively correlated with (p < 0.05), but had no correlation with FC or MRR (p > 0.05). There were no correlations for milk yield with RC, FC, or MRR (p > 0.05). Positive correlations were observed for fat corrected milk yield with GRSM and RMSC (p < 0.05). Fat production (kg dayâ€’1) was positively correlated with GRSM and RMSC (p < 0.05). The gross revenue from the sale of milk and the revenue minus feed costs showed to be highly associated with production variables.